Role of private providers in the implementation of the national health insurance scheme in Zambia: a qualitative study of perceptions and experiences - Jesper Sundewall; Warren Mukelabai Simangolwa (BMJ Open)
Introduction An increasing number of sub-Saharan African countries are implementing national health insurance schemes (NHISs) to support the aspiration of universal health coverage (UHC). A growing body of literature recognises the private sector role in improving NHIS equity in service access, public provider complementarity and overall member satisfaction. Zambia has implemented the NHIS since 2019 as a priority health financing strategy to support UHC. This study provides the first examination of the private sector’s experiences implementing the Zambia NHIS.Methods The study uses a qualitative study design and inductively synthesises data from 30 in-depth interviews with the private sector accredited to the Zambia NHIS in one rural and one urban province.Results The private sector was motivated by profits and complementarity with public providers regarding service readiness and availability. Providers perceived the accreditation process and fees as standard and affordable. Providers reported increased service utilisation, mainly by the NHIS clients. Senior citizens and the informal sector constituted the majority of users. There were implementation challenges, including delays in preauthorisations, loss of member details and exclusion and restrictions of interventions in the benefits package. Private providers also experienced overcrowding and reduced service quality. Providers perceived the service reimbursement levels as relatively cost-reflective, but some providers shifted models to maximise profits, including inducing demand to defraud the fund. Generally, providers perceived payments as within the agreed timelines, especially for online claims.Conclusion The initial scepticism among private providers before the initiation of the NHIS has subsided. The private provider’s experiences with accreditation, service utilisation, claims and reimbursements have been overall positive.